PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE, FASILITAS PERPAJAKAN DAN KOMISARIS INDEPENDEN TERHADAP MANAJEMEN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PADA TAHUN 2012-2014 - Hesty Rahmawati; M. Rasuli; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study was conducted on manufacturing companies listed on Indonesia Stock Exchange on years 2012-2014. The sample technique on this research was with purposive sampling technique. Which the total sample is used 45 companies. Data analysis was conducted used multiple regression model with help of software SPSS version 21.00. Independent variables used in this study are size, profitability, leverage, taxation facilities and independent commissioners. While dependent variable in this study is the tax management. This study aimed to determine the influence of size, profitability, leverage, taxation facilities and independent commissioners to the tax management on manufacturing companies listed on Indonesia Stock Exchange period 2012 to 2014. Of the result of this study indicated that size, profitability and independent commissioners did not influence on the tax management. While leverage and taxation facilities influence on the tax management.Keywords: Size, Profitability, Leverage, Taxation Facilities, Independent Commissioners and Tax Management